Pengaruh Teknologi Informasi Terhadap Kinerja Organisasi Universitas Kota Padang Dengan Budaya Organisasi Sebagai Variabel Moderasi - Elsa Meirina; Mike Kusuma Dewi (JURNAL PUNDI, 2021)
Higher education is a higher education organizing unit as an advanced level of secondary education in the education pathway and has a strategic function, namely as a cultural center, the development of science and technology and as a moral force. This situation can be realized if well managed and able to show the resources in an organization that play a role in achieving success. The problem that arises is that universities have experienced fundamental changes that have never happened before, namely problems related to organizational performance, especially universities in the city of Padang, as a whole is not optimal, this is indicated by the implementation of services related to complicated student UKT payments, inadequate qualifications of lecturer workforce the number of student applicants and students accepted is small and the number of published studies and publications is relatively limited due to the system. In this study, the hypothesis is obtained that information technology (X) has a positive and significant effect on organizational performance at the University in Padang City. This can be seen from the significance value (sig.) Of information technology of 0.000 <0.05 and organizational culture (Z) moderates the significant influence of information technology (X) on organizational performance (Y). the real level is 0.05. Data processing using SPSS Ver.25.Keyword: Information technology, Organizational performance, Organizational Culture